Perceived Effects of Tutors’ Pedagogical skills on Academic Performance of Pre-service Deaf teachers at the Presbyterian College of Education, Akropong Akuapem - Brew, Bright (European Journal of Applied Sciences, 2022)
This study explored the perceived effect of tutors’ pedagogical skills on the academic performance of pre-service Deaf teachers at the Presbyterian College of Education, Akropong Akuapem. The research design used was phenomenology where eight pre-service Deaf teachers were purposively sampled for the study. Data was collected by using face-to-face semi-structured interviews. Thematic analysis was employed to analyse the data. The results of the study showed that tutors’ way of presentation makes it difficult for pre-service teachers who are deaf at the Presbyterian College of Education, Akropong Akuapem to understand what is taught. Again, it was found out that most tutors in the College could not use the Sign Language effectively; therefore, they were not able to effectively communicate with pre-service teachers who are deaf. Furthermore, it was revealed that pre-service teachers who are deaf preferred practically oriented and demonstration lessons to the theoretical style of learning to understand concepts taught. The paper concludes that some tutors’ way of teaching negatively affect the academic performance of pre-service Deaf teachers at the Presbyterian College of Education.